5,22-Stigmastadien-3 beta-yl p-toluenesulfonate - Ketuly, K.A.; Hadi, A.H.A.; Khaledi, H.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The asymmetric unit of the title compound {systematic name: (3S,8S,9S,10R,13R,14S,17R)-17-[(E,2R,5S)-5-ethyl-6-methylhept-3-en-2-y l]-10,13-dimethyl-2,3,4,7,8,9,11,12,14,15,16,17-dodecahydro-1H-cyclopent a[a]phenanthren-3-yl p-toluenesulfonate}, C(36)H(54)O(3)S, comprises two independent molecules that differ significantly in terms of the relative orientations of the peripheral groups; the conformation about the C=C bond of the side chain is E. In the crystal, molecules associate into linear supramolecular chains aligned along the a axis via C-H center dot center dot center dot O interactions.